(Bio)medicine meets Art: A physiologist’s reflections on inter-disciplinary liaisons, curriculum renewal and pursuing social justice - Essop, Faadiel (Critical Studies in Teaching and Learning, 2025)
This self-reflective article focuses on interdisciplinary intersections between Science, Medicine, and the Arts. It traces the journey of the author, a physiologist, starting with a visual redress project initiated with the late Professor Elmarie Costandius (Visual Arts, Stellenbosch University). The nature of such interactions is considered, revealing the remarkable personality of Professor Costandius, and the unique methodologies she employed to ensure the project’s completion.  This project resulted in the author identifying a knowledge gap in the training of science and medical students and thereafter pursuing curriculum renewal for postgraduate students (Features of Science module, Faculty of Medicine and Health Sciences, Stellenbosch University).  There is some reflection on the nature and outcomes of the module, and an exercise that involved Arts and Biomedical students discussing artworks relating to the heart.  It is proposed that such inter-disciplinary liaisons can elicit serendipitous outcomes in terms of teaching and learning, and biomedical research pursuits.